1974
DOI: 10.1007/bf02636021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of products from clay catalyzed polymerization of tall oil fatty acids

Abstract: Products obtained by acid clay catalyzed dimerization of oleic, elaidic, and tall oil fatty acids were characterized. The monomeric products (35% of total) consisted of stearic, octadecenoic (66% trans-), and mid chain monomethyl branched acids, both saturated and unsaturated. The polymeric products (65% of total) consisted of linear, alicyclic, aromatic, and polycyclic dimers. The tall oil fatty acid based dimer closely resembled oleic dimer in polycyclic character and linoleic dimer in aromatic and linear st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…The branched-chain acids have the same number of carbons as the parent acid in the feed. From tall oil fatty acids, methyl branching predominates with a branch methyl group to acid ratio of about 1.3 (16).…”
Section: Background In the Synthesis Of Branched-chain Fatty Acidsmentioning
confidence: 99%
“…The branched-chain acids have the same number of carbons as the parent acid in the feed. From tall oil fatty acids, methyl branching predominates with a branch methyl group to acid ratio of about 1.3 (16).…”
Section: Background In the Synthesis Of Branched-chain Fatty Acidsmentioning
confidence: 99%
“…The branched-chain acids have the same number of carbon atoms as the parent acids in the feed. From tall oil fatty acids, methyl branching predominates with a branch methyl group to acid ratio of about 1.3 [13].…”
Section: Introductionmentioning
confidence: 99%
“…In 1994, Neuss et al [3] reported that, with a montmorillonite clay catalyst in combination with an active carbon, sunflower oil FA/ esters could be converted to bc-isomers in yields between 30 and 40%. Although bc-acids can be synthesized using clay catalysts [4], there are several drawbacks to using them. First, conversion of the linear UFA is modest at best and, secondly, the clay catalysts give primarily oligomeric byproducts (mainly dimers and trimers) and thus have a rather low selectivity to bc-FA.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the four types of zeolites referenced above all have uni-dimensional channels. The rigid aluminosilicate networks are made up of tetrahedral SiO 4 and AlO 4 molecules and possess negative charges in the framework wherever the tetravalent Si is replaced by the trivalent Al. In order to balance the charges, zeolites typically contain counter ions such as Na 1 , K 1 , Ca 21 , NH 4 1 and H 1 inside the cavities and channels [12].…”
Section: Introductionmentioning
confidence: 99%